Clinicopathological Features of Stage I–III Colorectal Cancer Recurrence Over 5 Years After Radical Surgery Without Receiving Neoadjuvant Therapy: Evidence From a Large Sample Study - Luo, Dakui; Yang, Yufei; Shan, Zezhi; Liu, Qi; Cai, Sanjun; Li, Qingguo; Li, Xinxiang (Frontiers in Surgery, 2021)
Late recurrence (five or more years) after radical resection of colorectal cancer is rare. Our present study aims to investigate the features of late recurrence in stage I-III colorectal cancer. A total of 9754 stage I-III colorectal cancer patients who underwent radical surgery without receiving neoadjuvant therapy in Fudan University Shanghai Cancer Center were enrolled in this study. These patients were divided into three groups: early recurrence (3 month-2 years), intermediate recurrence (2 years-5 years) and late recurrence (over 5 years). The median duration of follow-up was 53.5±30.1 months. 2341 (24.0%) patients developed recurrence. The late recurrence rate was 11.7%. Patients with higher risk of late recurrence were more likely to be older, to be T4, to have more colon cancer, to have less disease of signet ring cell histology, to have less poor differentiated tumors, to have less stage III disease, perineural invasion and vascular invasion. Multivariate logistic regression analysis identified age, differentiation, T stage, N stage, perineural invasion and vascular invasion as independent factors for late recurrence. Late recurrent colorectal cancer has some distinctive characteristics. Although recurrence over five years after surgery is infrequent, an enhanced follow-up is still needed for the selected patients after five years.